Note sur les fondements des postcolonial studies - Béatrice Collignon (EchoGéo)
Long ignored by French social sciences, the term "postcolonial" has recently become popular in academic literature and meetings, in relation to the political debate about colonial legacy and 2nd and 3rd immigrants generations (the so-called "indigènes de la République"). Yet, although the term is the same ("postcolonial"), the meaning it is usually given in France by those who qualify their work as such is quite different from the one it has in the anglo world. In this context, this note aims at clarifying the situation for French geographers and others by presenting briefly some of the main aspects of postcolonial theory.